2023
DOI: 10.3390/life13020278
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Asthma Is Associated with Reduced Sperm Count—A Cross-Sectional Study of More than 6000 Young Men from the General Population

Abstract: Asthma is driven by an inflammatory response that may impact testicular function. In this cross-sectional study, we investigated the association between self-reported asthma and testicular function (semen parameters, reproductive hormone levels), and determined whether potential further inflammation due to self-reported allergy modified this association. A total of 6177 men from the general population completed a questionnaire including information on doctor-diagnosed asthma or allergy, had a physical examinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…In addition, only one cross-sectional study in humans found a potential association between self-reported asthma patients and reduced testicular function, primarily manifested by decreased spermatozoa concentration and total spermatozoa count. However, no significant differences were observed in semen volume, spermatozoa motility, or spermatozoa morphology ( Pedersen et al, 2023 ). The findings from the above studies have proved a negative correlation between asthma and spermatozoa quality.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In addition, only one cross-sectional study in humans found a potential association between self-reported asthma patients and reduced testicular function, primarily manifested by decreased spermatozoa concentration and total spermatozoa count. However, no significant differences were observed in semen volume, spermatozoa motility, or spermatozoa morphology ( Pedersen et al, 2023 ). The findings from the above studies have proved a negative correlation between asthma and spermatozoa quality.…”
Section: Discussionmentioning
confidence: 84%
“…As illustrated in animal models, male mice with asthma were related to abnormal spermatozoa and testicular structure ( Xu et al, 2016 ; Deng et al, 2021 ; Wang et al, 2021 ; Feng et al, 2022 ). Moreover, a cross-sectional study in humans showed that men with asthma had lower spermatozoa concentration and total spermatozoa count compared with non-asthmatic men ( Pedersen et al, 2023 ). The findings from the above studies have proved a negative correlation between asthma and spermatozoa quality.…”
Section: Introductionmentioning
confidence: 99%